SCHOLARS' PERSPECTIVES ON CONTEMPORARY DEVELOPMENTS IN LINGUISTICS - Rustamova Shakhnoza Abdurakhimovna (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Abstract: This article delves into scholars' perspectives on recent progressions within the domain of linguistics. By consolidating available literature and scholarly discussions, it scrutinizes the principal patterns, theories, and methodologies influencing modern linguistics. Through an assessment of scholars' viewpoints, this investigation seeks to offer valuable insights into the dynamic terrain of linguistic inquiry and its ramifications for forthcoming academic endeavors.